The trouble with lenders : subtleties in the debt Financing of commercial real estate - Furfine, Craig (London : Kellogg School of Management, 2016)
With interest rates near all-time lows in late 2015, Stanley Cirano knew it was an opportune time to consider the financing on his portfolio of commercial real estate. Cirano Properties was the general partner on three separate private equity investments of retail shopping centers in suburban Chicago. The first, Brookline Road Shopping Center, had been acquired in 2006 and had been managed through the financial crisis and real estate downturn. The property was performing well and Cirano wondered whether it made sense to refinance or sell. The second property, Columbus Festival Plaza, had been acquired in a 2010 bankruptcy auction. Although the property had needed a good amount of capital improvements, Cirano was proud of the growth in net operating income he had been able to generate. The final property, Deerwood Acres, had been developed by Cirano himself after acquiring the property in 2013 from the previous owner, who had been operating a go-cart track and drive-in theater on the land. Cirano expected great things from the property, though his lease-up had been slower than anticipated.Although the three properties had different levels of performance and presented different management issues, they all shared the fact that they were all significantly financed, in part, with debt. As the properties were acquired at different times, Cirano had simply selected what seemed like reasonable financing at the time. With his concern that interest rates would soon be rising, Cirano thought it made sense to take a holistic view of his portfolio, consider what debt options were available to him, and make a sound strategic decision on the financing of all his assets at the same time.
Originally published in Furfine, C. (2016). The trouble with lenders: Subtleties in the debt financing of commercial real estate. 5-315-507. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cirano, Stanley; Cirano Properties; Brookline Road Shopping Center; Columbus Festival Plaza; Deerwood Acres; Commercial real estate; Real estate investment -- Finance